UNEMPLOYMENT, POVERTY AND INCOME INEQUALITY IN NORTH SUMATRA PROVINCE - Ince Weya (Proceeding of The International Conference on Economics and Business, 2022)
. This study aims to determine how much influence unemployment and poverty have on the level of income inequality in North Sumatra Province. This research is a quantitative research using data analysis techniques Panel Data Regression with Random Effect Model. The data period used in the study is from 2017 - 2021 sourced from the Central Bureau of Statistics for North Sumatra Province. The results of this study are that unemployment has a positive and significant effect on income inequality in 33 districts/cities of North Sumatra province. Poverty has a negative and insignificant effect on income inequality in 33 districts/cities of North Sumatra province. Unemployment and poverty have a significant effect on income inequality.